Dire straits : the perils of writing the early modern English coastline from Leland to Milton - Bellamy, Elizabeth J. (Elizabeth Jane) (Toronto [Ont.] : University of Toronto Press, 2013)
By illustrating how early modern English writers created their works in the context of a longstanding cultural inheritance from antiquity, Elizabeth Jane Bellamy offers a new approach to the history of early modern cartography and its influences on literature.
4 Exiled Shorelines: Early Milton and the Rejection of the Mare Ovidianum. 1 'Love your Naso's name ... -- 2 Poetry, Place, and the Mare Ovidianum -- 3 Tomitan Ovid: Writing a Pontic Epic on the Apeiron -- 4 Rejecting the Pose of Ovidian Exile -- 5 'At last he twitch't his mantle': Lycidas and Milton's 'Writing' of Local Coastlines -- 6 The Londini Milto, Mansus, and the Thames -- 7 Milton, Horace, and Ovid in Geneva.
Includes bibliographical references (pages 185-200) and index.
5 Coda : Exiting the Shadow of Ultima Britannia in Paradise Lost.
English.
JSTOR
Keywords: English poetry -- Early modern, 1500-1700 -- History and criticism; Coasts in literature; Cartography in literature; Landscapes in literature; England -- In literature; Littoral dans la littérature.; Cartographie dans la littérature.; Paysages dans la littérature.; Angleterre -- Dans la littérature.; LITERARY CRITICISM -- Medieval; POETRY -- English, Irish, Scottish, Welsh; Cartography in literature; Coasts in literature; English poetry -- Early modern; Landscapes in literature; Literature; England; Frühneuenglisch; Literatur; Küste; 1500-1700; Criticism, interpretation, etc